ELISA technique standardization for strongyloidiasis diagnosis - Huapaya, Pedro (2002)
Objective: To standardize ELISA technique for human Strongyloides stercoralis infection diagnosis. Material and methods: A crude antigen was prepared using filariform larvae obtained from positive stool samples cultured with charcoal. Harvested larvae were crushed by sonication and washed by centrifugation in order to obtain protein extracts to be used as antigen. Final protein concentration was 600 µg/mL. Several kinds of ELISA plates were tested and antigen concentration, sera dilution, conjugate dilution and cut off were determined to identify infection. Sera from patients with both hyperinfection syndrome and intestinal infection demonstrated by parasitological examination were positive controls and sera from people living in non-endemic areas with no infection demonstrated by parasitological examination were negative controls. Results: Best values were 5 µg/mL for antigen, 1/64 for sera, 1/1000 for conjugate; optical density values for positive samples were 1,2746 (1,1065 – 1,4206, DS = 0,3284) and for negative samples 0,4457 (0,3324 – 0,5538, DS = 0,2230). Twenty sera samples from positive subjects and one hundred from negative subjects were examined, obtaining 90% sensitivity and 88% specificity. Conclusion: The results show this technique could be useful as strongyloidiasis screening test in population studies.